Investigating students’ attitudes towards translation technology: The status quo and structural relations with translation mindsets and future work self - Sha Tian; Lingxiao Jia; Zhining Zhang (Frontiers in Psychology, 2023)
IntroductionDespite the growing attention paid to the research of translation technology teaching (TTT), there is still a lack of studies on students’ attitudes and the motivational factors in relation to it. To this end, the paper reports on a questionnaire-based study that describes students’ attitudes towards translation technology (in the Chinese MTI context) and explores its structural relations with translation mindsets and future work self.MethodsData were collected from 108 grade 2021 MTI students of three selected Chinese universities and analyzed using descriptive statistics and structural equation modeling (SEM).ResultsThe results demonstrate that Chinese MTI students’ overall attitudes towards translation technology are slightly positive. So far, they perceive translation technology to be slightly effective for translation and are slightly mindful of it. They are slightly influenced by teachers and still feel inhibited when learning and using it. Furthermore, the results also indicate that growth translation mindsets positively influence students’ attitudes towards the effectiveness of translation technology, teacher influence, exhibition to translation technology, and mindfulness about translation technology, whereas fixed translation mindsets only negatively predict students’ teacher influence. Likewise, future work self-salience positively associates with students’ attitudes towards the effectiveness of translation technology and mindfulness about translation technology, while future work self-elaboration positively relates to students’ exhibition to translation technology. Among them, growth translation mindsets are the strongest predictor for all attitudes components.DiscussionTheoretical and pedagogical implications are also discussed.